Chronic osteomyelitis with pathological fracture induced by Mycoplasma hominis infection: a case report and review of the literature - Zhu, Ling-Na; Shen, Wen-Bin; Zou, Xiao-Yan; Zuo, Jiang-Cheng; Xiao, Ning (Frontiers in Medicine, 2025)
Mycoplasma hominis, commonly residing in the genitourinary tract, can cause rare extragenital infections, especially in immunocompromised individuals. This report details a case of chronic osteomyelitis with a pathological femur fracture in a 79-year-old woman. Despite a history of bone tuberculosis, the infection was identified as Mycoplasma hominis through culture and mass spectrometry, highlighting the diagnostic challenges due to the organism’s lack of a cell wall. This case underscores the necessity for advanced diagnostic methods and awareness of Mycoplasma hominis in non-urogenital infections.